Population aging and international capital flows - David Domeij; Martin Floden (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
We use the neoclassical growth framework to model international capital flows in an economy with exogenous demographic change. We compare model implications and actual current account data and find that the model explains a small but significant fraction of capital flows between OECD countries, in particular after 1985.
Keywords: E22; F21; F41; F47; 330; current account; international capital mobility; demographics; Feldstein-Horioka puzzle; Kapitalmobilität; Leistungsbilanz; Demographie; Theorie